2021
DOI: 10.1111/apt.16438
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs, polygenic risk score and colorectal cancer risk

Abstract: Summary Background The regular use of non‐steroidal anti‐inflammatory drugs (NSAIDs) has been associated with reduced colorectal cancer (CRC) risk. Aim To explore whether this association varies according to background polygenic risk for CRC. Methods Data were collected from a large population‐based case‐control study on CRC in Germany. A polygenic risk score (PRS) based on 140 CRC‐related risk loci was used to quantify the genetic risk. The associations of regular use of NSAIDs (≥2times per week for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
(52 reference statements)
0
18
1
Order By: Relevance
“…The GRE has recently been developed as a novel approach for improving risk communication to the public. 20 , 21 , 22 For example, the large GRE for heavy drinking in our study indicates that the impact of reduced alcohol consumption could be as strong as the impact of having a substantially lower predetermined polygenic risk for CRC, in particular EOCRC, which might help improve adherence to healthy guidelines, especially for those with a high genetic predisposition to CRC. In addition, variations regarding the relationship of heavy drinking with CRC risk by cancer location, and the estimated high GRE for distal CRC in our study further underscore the importance of targeted CRC cancer prevention.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The GRE has recently been developed as a novel approach for improving risk communication to the public. 20 , 21 , 22 For example, the large GRE for heavy drinking in our study indicates that the impact of reduced alcohol consumption could be as strong as the impact of having a substantially lower predetermined polygenic risk for CRC, in particular EOCRC, which might help improve adherence to healthy guidelines, especially for those with a high genetic predisposition to CRC. In addition, variations regarding the relationship of heavy drinking with CRC risk by cancer location, and the estimated high GRE for distal CRC in our study further underscore the importance of targeted CRC cancer prevention.…”
Section: Discussionmentioning
confidence: 84%
“…GREs were calculated as the ratio of coefficients for alcohol consumption categories and PRS percentiles from logistic regression models, providing an estimate of alcohol impact in terms of the equivalent difference in background genetic risk. Details of the derivation of GREs have been published recently, 20 , 21 , 22 and described specifically for this study in the Supplementary Text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a similar conclusion was reached by a German study that found no heterogeneity of the association between colorectal cancer risk and non-steroidal anti-inflammatory drug use across strata of PRS. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In this large population-based study from Germany, we aimed to assess the association of red and processed meat intake with CRC risk across various levels of a PRS that incorporates information from 140 independent genetic variants on CRC risk [ 4 ]. Furthermore, we aimed to compare the effects of red and processed meat intake with the impact of genetic predisposition using “genetic risk equivalent” (GRE) [ 11 , 12 ], a recently developed metric aimed at enhancing effective risk communication.…”
Section: Introductionmentioning
confidence: 99%